Implementasi Kurikulum Merdeka Belajar dalam Pendidikan Agama Islam - Lilis Ani Rifatin Ningsih; Kiki Suliyatun; Imam Andrianto (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Prambon Public High School's Islamic Religious Education program, which follows the Independent Learning Curriculum, is the focus of this study. Participating in the study are students, instructors of Islamic religious education, the school principal, the curriculum and subject coordinators, and researchers who employ a phenomenological approach to qualitative research. The Independent Learning Curriculum is based on the principles of constructivism, which places the emphasis on the student as the primary agent of their own learning. Facilitators, teachers lead students through the steps of seeing, exploring, discussing, explaining, and developing and applying concepts. Teachers use diagnostic, formative, and summative assessments to evaluate student learning in keeping with the standards set out by the Independent Learning Curriculum. Based on the results, it seems that the implementation is student-centered, with instructors playing the role of guides. Within the context of the Independent Learning Curriculum, the implications offer recommendations for enhancing the standard of Islamic Religious Education instruction.